UPAYA PENINGKATAN PENJUALAN DAN DAYA SAING PADA “ANYA SHOP”MELALUI STRATEGI SWOT - Dewi, Asfita; Sriwitantiningsih, Luluk; Murti, Oktavia Wahyu Krisna; Widyastutie, Erika; Qomariah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia has experienced a significant increase because it is one of the activities that can be used as a means of livelihood that can create jobs both directly and indirectly for the community. This MSME is very helpful for individual micro entrepreneurs because it has proven to be able to overcome the economic crisis that has hit Indonesia. Various efforts by the government have been made to increase the development of MSMEs. The purpose of this research is to find out how the marketing strategy carried out by MSME Anya Shop increases sales. The type of research is qualitative with SWOT analysis. Data collection methods are interviews, documentation and observation. The results of this research show that the strategic analysis carried out has been effective and the SWOT strategy has been implemented to increase sales at Anya Shop MSMEs, namely by adding sales products, attractive product forms, adding human resources, using social media and maintaining product quality.